PENERAPAN METODE WATERFALL DALAM MEMBANGUN APLIKASI UNTUK PENGUJIAN JALUR DAN BANGUNAN PRASARANA KERETA API - Bima Haryo Samudra; Naeli Umniati (Universitas Gunadarma, 2023)
The waterfall development method is a method that used to build an application not only for mobile phone but also for desktop. The waterfall method is also called as a linear sequential method. Testing of railways infrastructure and track is an activity to maintain the feasibility of technical and operational of railways. This testing activity still use manual works, with pencil and paper to write test results plus no application that can integrate the data of test results from railways tester to the head of railways tester. It’s all make harder for the railways testers do their job. Railways tester is a someone that has fulfilled education and training for being tester, worked at least for 2 years in railways infrastructure field, and have license as a railways tester. In this journal discusses how to apply the waterfall method in build and design the application that can help solve the problems in railways infrastructure and track testing. The development of this application is use 5 phases which consists from phase 1 is requirement analysis, phase 2 is design, phases 3 is development, phase 4 is trial, and phase 5 is maintenance.